2004
DOI: 10.1038/sj.bjc.6602092
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Apaf-1 expression in human cutaneous melanomas

Abstract: Malignant melanoma is a life-threatening skin cancer due to its highly metastatic character and resistance to radio-and chemotherapy. It is believed that the ability to evade apoptosis is the key mechanism for the rapid growth of cancer cells. However, the exact mechanism for failure in the apoptotic pathway in melanoma cells is unclear. p53, the most frequently mutated tumour suppressor gene in human cancers, is a key apoptosis inducer. However, p53 mutation is only found in 15 -20% of melanoma biopsies. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
38
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 39 publications
8
38
0
1
Order By: Relevance
“…4,5 Moreover, our experiments correlating Apaf-1 expression with chemosensitivity were conducted blindlyone laboratory (YL) measured Apaf-1 expression and the other (SWL) assayed apoptosis and the results were compared later. Finally, we confirmed the immunoblotting results by Northern blotting and in situ hybridization 1 and, more recently, other investigators corroborated our observations using three different antibodies, [6][7][8][9] and by LOH analyses and quantitative RT-PCR. 10,11 Given that technical issues are unlikely to account for the differences between data sets, it is possible that the studies by Peltenburg and Allen did not examine enough samples to make reliable conclusions.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…4,5 Moreover, our experiments correlating Apaf-1 expression with chemosensitivity were conducted blindlyone laboratory (YL) measured Apaf-1 expression and the other (SWL) assayed apoptosis and the results were compared later. Finally, we confirmed the immunoblotting results by Northern blotting and in situ hybridization 1 and, more recently, other investigators corroborated our observations using three different antibodies, [6][7][8][9] and by LOH analyses and quantitative RT-PCR. 10,11 Given that technical issues are unlikely to account for the differences between data sets, it is possible that the studies by Peltenburg and Allen did not examine enough samples to make reliable conclusions.…”
supporting
confidence: 91%
“…11 Baldi et al, Dai et al, Zannon et al and Mustika et al report a heterogeneous expression of Apaf-1, highly positive in benign nevi but weak or undetectable in 35-50% in situ melanomas and lymph node and visceral metastases. [6][7][8][9] In addition, Qin et al have also independently reported low Apaf-1 expression in metastatic melanoma cell lines used in our initial study. 12 These results, along with recent reports of low Apaf-1 expression in other melanoma cell lines, 13 are consistent with our initial findings.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…In relation to tumor suppressor genes (TSGs), CDKN2A ranks as the gene most commonly deleted in melanoma, after which the PTEN (Packer et al, 2006), TP53 (Giglia- Mari and Sarasin, 2003) and APAF1 (Dai et al, 2004;Fujimoto et al, 2004;Mustika et al, 2005) genes show the highest frequency of inactivation in sporadic melanomas, principally through deletion, mutation and hypermethylation, respectively. Clearly, additional melanoma TSGs exist, and a large number of chromosomal loci showing loss of heterozygosity (LOH) have been implicated in melanoma development, highlighting widespread chromosomal instability (Curtin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the Apaf-1 gene could be turned back on by treating cultured melanoma cells with inhibitors of DNA methylation or histone deacetylation, and this treatment rescued the apoptotic defect and markedly enhanced the chemoresponsiveness of melanoma cells. 82 Subsequent studies performed in other laboratories have provided further support for this mechanism of Apaf-1 inactivation in metastatic melanomas, 83 although it should be noted that loss of Apaf-1 may not be the sole determinant of chemoresistance in this type of cancer. 84 Nevertheless, the fact that a substantial proportion of leukemia-derived cell lines and primary leukemic cells, 85 as well as cells from glioblastomas 86 and cervical carcinomas 87 may also inactivate Apaf-1 through a similar mechanism, further suggests that apoptosome deregulation may represent a significant event in human cancer.…”
Section: Apoptosome Dysfunction In Human Cancer: Mechanisms Of Apaf-1mentioning
confidence: 99%